The Effects of Physical Activity in Children and Adolescents with Developmental Coordination Disorder - Harilaos Zaragas; Olga Fragkomichelaki; Marina Geitona; Maria Sofologi; Georgia Papantoniou; Dimitrios Sarris; Vassiliki Pliogou; Christos Charmpatsis; Panagoula Papadimitropoulou (MDPI AG, 2023)
The purpose of this literature review was to detect and study the effectiveness of therapeutic intervention programs, such as physical activities and sports, on children and adolescents with Developmental Motor Coordination Disorder (DCD) to improve their motor skills. The sample for this study consisted of 48 (100%) papers, specifically, 40 (83.5%) articles, 3 (6.2%) doctoral theses, 2 (4.1%) master's theses and 3 (6.2%) papers from conference proceedings from the year 2014 to 2022. To search the sample, the following terms were used: DCD or dyspraxia, physical activity programs, intervention, physical intervention, physical education, etc. The results for the existence of statistically significant results and internal validity of intervention programs using physical activities and sports in children and adolescents with DCD showed that a large number of intervention programs improved the children's motor skills as well as their daily functionality. In contrast, other interventions failed to improve dynamic and static balance. The negative result could be due either to the short duration of the interventions or to the improper suboptimal design-organization of the methodology of these programs-such as the heterogeneous intervention samples and the use of inappropriate and reliable assessment tools.